Changes in Serum Betatrophin Levels in Obese Women after Two-Weeks of Moderate-intensity Aerobic Exercise - Mubasyiroh, Nabila Ainaya; Sugiharto, Sugiharto; Merawati, Desiana; Fathil, Nur Ezza Fazleen Mohd; Rejeki, Purwo Sri; Widyatama, Fikri Sasongko; Pranoto, Adi (Faculty of Sport and Health Sciences, 2024)
Obesity is associated with increased betatrophin levels, which can lead to fat metabolism disorders. Increased levels of betatrophin may inhibit the performance of the lipoprotein lipase (LPL) enzyme, making it difficult for triglycerides (TG) in the blood to be converted into energy and causing excessive fat accumulation in adipose tissue. Physical exercise has been reported to increase energy expenditure in obesity. This study aims to determine changes in betatrophin in obese women after moderate-intensity aerobic exercise. A total of twenty obese women aged 20-30 years took part in the study. The participants were administered into two groups: control (K1) and moderate-intensity aerobic exercise (K2). Moderate-intensity aerobic exercise (60-70% HRmax) was performed five times a week for two weeks. Pretest and posttest betatrophin levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) Kit method. Data were analyzed using a paired samples t-test with a significance level of p ≤ 0.05. The results showed the average pretest and posttest betatrophin levels in K1 (0.44±0.14 vs 0.44±0.13 ng/mL; p=0.894), and K2 (0.41±0.05 vs 0.31±0.03 ng/mL; p=0.000). According to the study's findings, moderate-intensity aerobic exercise (60-70% HRmax) performed five times per week for two weeks positively impacted alterations in betatrophin levels in obese women.